2001
DOI: 10.1002/1097-4652(2001)9999:9999<00::aid-jcp1051>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotrophin induces angiogenesis: Involvement of the phosphoinositide-3 kinase but not the nitric oxide synthase pathways

Abstract: Pleiotrophin (PTN) is a developmentally regulated protein that has been shown to be involved in tumor growth and metastasis presumably by activating tumor angiogenesis. To clarify the potential angiogenic activity of PTN and to analyze the signaling pathways involved in this process, we used an in vitro model of Human Umbilical Vein Endothelial Cells (HUVEC). We show that PTN was mitogenic toward a variety of endothelial cells including HUVEC, stimulated HUVEC migration across a reconstituted basement membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
47
1
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 28 publications
2
47
1
7
Order By: Relevance
“…For instance, HARP at a concentration of 3 nM caused a 50% inhibition of VEGF 165 -induced proliferation and almost completely abolished VEGF 165 -induced migration and differentiation without affecting the behavior of unstimulated HUVEC cultured without VEGF 165 . These results contrast with those obtained previously with microvascular endothelial cells (Papadimitriou et al, 2001) or on HUVEC stimulated with partially purified supernatants of cells overexpressing HARP (Souttou et al, 2001). In agreement with our results, we have not detected in HUVEC mRNA expression of anaplastic lymphoma kinase, a receptor that transduces HARPmediated signals.…”
Section: Discussionsupporting
confidence: 72%
“…For instance, HARP at a concentration of 3 nM caused a 50% inhibition of VEGF 165 -induced proliferation and almost completely abolished VEGF 165 -induced migration and differentiation without affecting the behavior of unstimulated HUVEC cultured without VEGF 165 . These results contrast with those obtained previously with microvascular endothelial cells (Papadimitriou et al, 2001) or on HUVEC stimulated with partially purified supernatants of cells overexpressing HARP (Souttou et al, 2001). In agreement with our results, we have not detected in HUVEC mRNA expression of anaplastic lymphoma kinase, a receptor that transduces HARPmediated signals.…”
Section: Discussionsupporting
confidence: 72%
“…Others have reported that bacterially produced peptides and full-length pleiotrophin can induce endothelial cells to form tubes in vitro (Papadimitriou et al, 2001). Souttou et al (2001) also found migratory and tube formation effects on human umbilical vein endothelical cells treated with pleiotrophin. These findings are thus compatible with the idea that pleiotrophin can exert an angiogenic effect.…”
Section: Discussionmentioning
confidence: 88%
“…PTN has been reported to be mitogenic for endothelial and epithelial cells, as well as for fibroblasts (Li et al 1990;Fang et al 1992;Delbe et al 1995;Souttou et al 1997Souttou et al , 2001). However, also antiproliferative effects on chondrocytes have been reported (Tapp et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Mature PTN is a non-glycosylated, lysine-rich peptide that migrates anomalously as an 18-kDa band in sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) (therefore also termed p18; Corbley 1997) and is derived from a 168-residue precursor with a 32 amino acid signal sequence. PTN is mitogenic for various cell types, it promotes angiogenesis, stimulates neurite outgrowth from cultured neurones, and induces cell migration (Li et al 1990;Fang et al 1992;Delbe et al 1995;Souttou et al 1997Souttou et al , 2001Rauvala et al 2000). Together with midkine (MK) it forms a family of heparin-binding proteins that are normally expressed during embryogenesis, but rarely in healthy adult tissues (Iwasaki et al 1997).…”
mentioning
confidence: 99%